2019
DOI: 10.31272/jeasd.23.6.13
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Behavior of Hybrid Reinforced Concrete Beams Combining Ultra High Strength Concrete and Porecilenite Aggregate Lightweight Concrete

Abstract: The main objective of this research was studied the flexure behavior of hybrid reinforced concrete beams combining reactive powder concrete (RPC) and lightweight concrete (LWC). The experimental work consists of casting and testing in flexure seven simply supported reinforced concrete beams. The dimensions of (7) beams were geometrically similar, having rectangular cross-section, of dimensions (125×200×1600) mm. Lightweight concrete was used in tension layer and reactive powder concrete was used in compression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Figure 5 illustrates the usual load-defection profles for the studied beam specimens. Tat load-defection response of the experimentally tested reinforcement concrete beams can be divided into phases as follows: linear elastic up to frst cracking, postcracking stage with multiple crack growth, yielding of tension reinforcement stage, and deformation due to plasticity phase with gradual loss of load carrying capacity until failure [20].…”
Section: Behavior Of Load Defectionmentioning
confidence: 99%
“…Figure 5 illustrates the usual load-defection profles for the studied beam specimens. Tat load-defection response of the experimentally tested reinforcement concrete beams can be divided into phases as follows: linear elastic up to frst cracking, postcracking stage with multiple crack growth, yielding of tension reinforcement stage, and deformation due to plasticity phase with gradual loss of load carrying capacity until failure [20].…”
Section: Behavior Of Load Defectionmentioning
confidence: 99%
“…Given the challenge of finding a single material that possesses all desired properties to a satisfactory level, engineers are tasked with optimizing the use of different materials and construction methods (Yam,1981). Hybrid layered systems, incorporating various strength materials, have found application in civil engineering construction (Abtan and Jaber, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that there was an increase in cracking and ultimate load and redaction in deflection by increasing the thickness of the reactive powder concrete layer. The type of failure was flexural mode for all models examined (Abtan and Jaber, 2016). Hisham et al studied the flexural behavior of hybrid tee beams The experimental results showed that using reactive powder concrete (RPC) in the web and normal strength concrete in the flange effectively enhanced performance of hybrid Tsection beams when compared with normal strength concrete T-beam, however, the increases in the first crack load, ultimate flexural load and ultimate deflection were 86.67%, 60% and 29.19% respectively, while, the increases for the case of using RPC in the flange and normal strength concrete in the web were 20%, 34.28% and 14.97 respectively when compared with normal strength concrete T-beam (Al-Hassani et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In hybrid systems, high-strength concrete can withstand compressive force at the top zone of the beam, while LWC offers the advantage of being lightweight at the rest of the section. Many researchers studied the behavior of conventional hybrid beams consisting of two types of concrete and achieved promising results [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%